Studying Multisensory Processing and Its Role in the Representation of Space through Pathological and Physiological Crossmodal Extinction - Jacobs, Stéphane; Brozzoli, Claudio; Hadj-Bouziane, Fadila; Meunier, Martine; Farnè, Alessandro (Frontiers in Psychology, 2011)
The study of crossmodal extinction has brought a considerable contribution to our understanding of how the integration of stimuli perceived in multiple sensory modalities is used by the nervous system to build coherent representations of the space that directly surrounds us. Indeed, by revealing interferences between stimuli in a disturbed system, extinction provides an invaluable opportunity to investigate the interactions that normally exist between those stimuli in an intact system. Here, we first review studies on pathological crossmodal extinction, from the original demonstration of its existence, to its role in the exploration of the multisensory neural representation of space and the current theoretical accounts proposed to explain the mechanisms involved in extinction and multisensory competition. Then, in the second part of this paper, we report recent findings showing that physiological multisensory competition phenomena resembling clinical crossmodal extinction exist in the healthy brain. We propose that the development of a physiological model of sensory competition is fundamental to deepen our understanding of the cerebral mechanisms of multisensory perception and integration. In addition, a similar approach to develop a model of physiological sensory competition in nonhuman primates should allow combining functional neuroimaging with more invasive techniques, such as transient focal lesions, in order to bridge the gap between works done in the two species and at different levels of analysis.